INVESTORS’ PREFERENCES FOR CASH DIVIDENDS: THE ROLE OF SELF-CONTROL AND DEMOGRAPHICS - Basharat Khan; Zulfiqar Ali; Mustansar Hayat; Amjad Iqbal (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the impact of an important emotional bias i.e. self-control and various demographic factors such as age, sex, marital status, academic qualification on investors’ preferences for cash dividends. The data required was gathered through questionnaires from 201 investors of the Pakistan Stock Exchange (PSX). Results of the study reveal that investors with low self-control tend to favor cash dividends more strongly than those investors having more resistance to temptation. Likewise, male investors exhibited a higher level of preference for cash dividends compared to their female counterparts. Investors holding a PhD showed significantly lower preferences for cash dividends as compared to those with secondary education. Married investors displayed slightly lower preferences for cash dividends compared to single investors. The observed preferences between younger and older investors was not significantly different.